Compounds Released by the Biocontrol Yeast Hanseniaspora opuntiae Protect Plants Against Corynespora cassiicola and Botrytis cinerea - Ferreira-Saab, Mariana; Formey, Damien; Torres, Martha; Aragón, Wendy; Padilla, Emir A.; Tromas, Alexandre; Sohlenkamp, Christian; Schwan-Estrada, Kátia R. F.; Serrano, Mario (Frontiers in Microbiology, 2018)
Plant diseases induced by fungi are among the most important limiting factors during pre- and post-harvest food production. For decades, synthetic chemical fungicides have been used to control these diseases, however, increase on worldwide regulatory policies and the demand to reduce their application, have led to searching for new ecofriendly alternatives such as the biostimulants. The commercial application of yeasts as biocontrol agents, has shown low efficacy compared to synthetic fungicides, mostly due to the limited knowledge of the molecular mechanisms of yeast-induced responses. To date, only two genome-wide transcriptomic analyses have characterized the mode of action of biocontrols using the plant model Arabidopsis thaliana, missing, in our point of view, all its molecular and genomic potential. Here we describe that compounds released by the biocontrol yeast Hanseniaspora opuntiae (HoFs) can protect Glycine max and Arabidopsis thaliana plants against the broad host-range necrotrophic fungi Corynespora cassiicola and Botrytis cinerea. We show that HoFs have a long-lasting, dose-dependent local and systemic effect against Botrytis cinerea. Additionally, we performed a genome-wide transcriptomic analysis to identify genes differentially expressed after application of HoFs in Arabidopsis thaliana. Our work provides novel and valuable information that can help researchers to improve HoFs efficacy in order for it to become an ecofriendly alternative to synthetic fungicides.